2015
DOI: 10.1016/j.febslet.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C attenuates insulin signaling transduction by promoting endoplasmic reticulum stress in hepatocytes

Abstract: a b s t r a c tIt has been reported that cystatin c (Cys C) closely correlates with metabolic disorders such as obesity and diabetes. However, it is still unknown whether Cys C plays a role for these disorders. Our results showed that the insulin signal transduction was largely impaired by Cys C in hepatocytes. In myotubes, however, the insulin signal transduction was not affected. Following experiments revealed that Cys C could induce endoplasmic reticulum stress (ER stress) in hepatocytes, whereas Cys C had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Circulating CysC is not only increased in kidney failure, but also in obese humans and mice (21,22). Consistently, we found increased circulating CysC levels in uninephrectomized as well as in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 86%
“…Circulating CysC is not only increased in kidney failure, but also in obese humans and mice (21,22). Consistently, we found increased circulating CysC levels in uninephrectomized as well as in HFD-fed mice.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we found that application of CysC attenuated insulin signal transduction in hippocampal neurons. This is in line with our previous finding that CysC impairs insulin signal transduction in hepatocytes [5]. These data imply that CysC is a detrimental factor for health.…”
Section: Dear Editorsupporting
confidence: 93%
“…Next, we explored the mechanism underlying the CysCmediated blockade of insulin signal transduction in primary hippocampal neurons. It has been shown that CysC attenuates insulin signal transduction in hepatocytes by inducing ER stress [5]. Therefore, we measured the ER stress-related genes Grp78, Chop, and Erdj4 and the results showed that CysC had no effect on their expression (data not shown).…”
Section: Dear Editormentioning
confidence: 93%
See 1 more Smart Citation
“…Our results showing high levels of salivary amylase and plasma lactate are consistent with involvement of the autonomic nervous system in the acute expression and secretion of type-2 cystatins from salivary glands. However, it is still possible that an increase in type-2 cystatin expression or secretion in saliva receives contributions from other tissues, since exercise leads to an increase in sympathoadrenal activity throughout the body [59]. Overall, in the 24 samples collected from the athletes for the two protocols in Fig 3, 83% showed an increase in cystatin secretion in saliva immediately after both aerobic and anaerobic tests.…”
Section: Discussionmentioning
confidence: 99%